2,6-Bis(phenylamino)-4-(iminophenyl)benzoquinone - M. John Plater (Molbank, 2022)
The reaction of 2,4-difluoronitrobenzene with an excess of aniline at 175 °C led to the isolation of an unexpected brown quinone substituted with two phenylamino groups and one phenylimino group. This product was easily distinguished from other expected derivatives because it is brown rather than yellow. The UV/Vis has a weak long wavelength absorption at 480–600 nm accounting for the colour.